1997
DOI: 10.1128/mcb.17.5.2669
|View full text |Cite
|
Sign up to set email alerts
|

Long-Range Interactions at theHOPromoter

Abstract: The SWI5 gene encodes a zinc finger DNA-binding protein required for the transcriptional activation of the yeast HO gene. There are two Swi5p binding sites in the HO promoter, site A at ؊1800 and site B at ؊1300. Swi5p binding at site B has been investigated in some detail, and we have shown that Swi5p binds site B in a mutually cooperative fashion with Pho2p, a homeodomain protein. In this report, we demonstrate that Swi5p and Pho2p bind cooperatively to both sites A and B but that there are differences in bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
53
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(56 citation statements)
references
References 26 publications
3
53
0
Order By: Relevance
“…At the HO promoter, a Pho2 binding site is located next to a Swi5 binding site, and it was shown that the two proteins bind to their sites cooperatively in vitro (7). However, recent in vivo data indicate that the role of Pho2 in HO regulation is complex (18). In the case of the HIS4 promoter, a Pho2 (Bas2)-protected region largely overlaps the Bas1 footprint.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the HO promoter, a Pho2 binding site is located next to a Swi5 binding site, and it was shown that the two proteins bind to their sites cooperatively in vitro (7). However, recent in vivo data indicate that the role of Pho2 in HO regulation is complex (18). In the case of the HIS4 promoter, a Pho2 (Bas2)-protected region largely overlaps the Bas1 footprint.…”
Section: Discussionmentioning
confidence: 99%
“…In the framework of this model, the deletion of amino acids 200 to 247 in our experiments, which results in the in-VOL. 18,1998 Pho2-Pho4 INTERACTIONS AT THE PHO5 PROMOTER 2637 on May 9, 2018 by guest http://mcb.asm.org/ ability of Pho4 to interact with Pho2, would destroy the internal interaction in the Pho4 protein, thus exposing the activation domain and in effect bypassing the Pho2 requirement. A second role for Pho2 can also explain our finding that the loss of promoter activity due to mutation of Pho2 cis elements can be almost fully compensated for by overexpression of Pho4 in a PHO2 strain, while the same is not true for the loss of promoter activity due to elimination of Pho2 itself.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The complex dynamics of gene expression during the cell cycle and after subjecting cells to stress have been assayed by ChIP analysis of the regulatory TFs and coactivators (McBride et al 1997;Bhoite et al 2001;Simon et al 2001;Horak et al 2002;Tan et al 2008;Ni et al 2009). Similarly, during sporulation (Kahana et al 2010) and glucose starvation (Young et al 2003;Tachibana et al 2005;Ratnakumar and Young 2010) multiple TFs bind upstream of the promoter of coregulated genes.…”
Section: Uas Function and Combinatorial Controlmentioning
confidence: 99%
“…Swi5 recognizes two sites in the HO promoter, called site A and site B, located approximately 1,800 and 1,300 nucleotides, respectively, upstream from the transcription start site (24,37). Swi5 binds to both of these sites with relatively low affinity, and binding by Pho2 is extremely weak.…”
mentioning
confidence: 99%